The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1590/s0001-37652003000100007
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic analysis in species of the genus Dasyprocta (Rodentia: Dasyproctidae) found in Brazilian Amazon

Abstract: A total of 30 animals of the genus Dasyprocta were cytogenetically studied. They belong to the following species: D. prymnolopha (N=20), D. leporina (N=6), D. fuliginosa (N=1) and Dasyprocta sp. (N=3) (Dasyproctidae, Hystricognathi). Cell suspensions were obtained by peripheral blood culture, besides bone marrow and spleen cells, from D. prymnolopha and D. leporina. The diploid number was 64/65 for all samples. The karyotypes showed similarity, and chromosomal polymorphism was not detected by Giemsa convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
5
0
6
Order By: Relevance
“…There is no cytogenetic data known for three species (Table 1). The diploid number in the Family varied from 62 to 65, and in the genus Dasyprocta, from 64 to 65, due to the presence of B chromosomes in four species (Ramos et al 2003). …”
Section: Resultsmentioning
confidence: 99%
“…There is no cytogenetic data known for three species (Table 1). The diploid number in the Family varied from 62 to 65, and in the genus Dasyprocta, from 64 to 65, due to the presence of B chromosomes in four species (Ramos et al 2003). …”
Section: Resultsmentioning
confidence: 99%
“…The most common for mammals is frequent appearance of intraindividual variability that can feature the same tissue or appear between different tissues. Mosaicism for the number of Bs was scored in Echymipera kalubu [ 22 ], Rattus rattus [ 103 ], V. vulpes [ 117 ], Myotis macrodactylus [ 28 ], A. peninsulae [ 118 ], Dicrostonix torquatus [ 119 ], Trinomys iheringi [ 113 ], Nictereutes procionides viverinus , Capreolus pygargus [ 44 ], Alouatta seniculus [ 32 ], Dasyprocta fuliginosa , Dasyprocta leporine , Dasyprocta prymnolopha [ 72 ], Apodemus flavicollis [ 11 ], Nictereutes procionides procyonides [ 120 ], Mazama nana [ 51 ], Mazama americana [ 51 ], Grammomys macmillani [ 78 ], Acomys ngurui , Tscherskia triton [ 121 ] and Mazama nemorivaga [ 52 ].…”
Section: Frequency Of B Chromosomesmentioning
confidence: 99%
“…Cytogenetic studies are essential because each species is characterized by a typical karyotype, which may differ from others with respect to form, size, and number of chromosomes (Lima, 2000). By cytogenetic analysis of 30 animals of the genus Dasyprocta (D. prymnolopha, D. leporina, and D. fuliginosa), Ramos et al (2003) identified that the individuals presented two cellular lineages, with 2n = 64 and 2n = 65 chromosomes. The karyotypes showed similarity, and chromosomal polymorphism was not detected by Giemsa conventional staining and G banding.…”
Section: General Characteristics Of Male and Female Agoutimentioning
confidence: 99%
“…This variation was observed with a frequency of approximately 70% in cells with 2n = 64 and 30% in cells with 2n = 65. There was no variation in the pattern of nucleolus organizer regions (NORs) in the species studied, which was used to verify chromosomal polymorphism (Ramos et al, 2003).…”
Section: General Characteristics Of Male and Female Agoutimentioning
confidence: 99%